2021
DOI: 10.1016/j.clinpr.2021.100089
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate use of REGN-COV2 in the treatment of COVID-19 in a patient with impaired humoral immunity

Abstract: Background The role of antibodies in coronavirus disease 2019 (COVID-19) in patients with X-linked agammaglobulinaemia (XLA) has yet to be characterised and clinical courses observed in this cohort of patients have been heterogeneous. Whilst some exhibit spontaneous recovery, others have experienced a more protracted disease length. Previous reports have described successful use of convalescent plasma, however there is a paucity of information around the use of the REGN-COV2 antibody cocktail in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Interestingly, in our cases there was limited evidence of a clinical or virological response to remdesivir in vivo. Similar findings have been observed elsewhere [ 23 , 28 ], in situations where in vitro sensitivity of the SARS-CoV-2 isolate has been demonstrated [ 28 ], although in other reports a response to remdesivir was seen, albeit followed by viral recrudescence [ 14 , 19 , 36 , 39 , 40 ]. It remains an open question whether remdesivir is needed as an adjunct to REGN-COV2 or other mAb therapies in the management of chronic COVID-19 in immunocomromised patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, in our cases there was limited evidence of a clinical or virological response to remdesivir in vivo. Similar findings have been observed elsewhere [ 23 , 28 ], in situations where in vitro sensitivity of the SARS-CoV-2 isolate has been demonstrated [ 28 ], although in other reports a response to remdesivir was seen, albeit followed by viral recrudescence [ 14 , 19 , 36 , 39 , 40 ]. It remains an open question whether remdesivir is needed as an adjunct to REGN-COV2 or other mAb therapies in the management of chronic COVID-19 in immunocomromised patients.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, this patient had evidence of vRNA in bronchoalveolar lavage which was absent from the upper respiratory tract. Nguyen and colleagues reported effectiveness of REGN-COV2 in combination with remdesivir in a patient with X-linked agammaglobulinaemia (XLA) and persistent COVID-19 [ 23 ]. Conversely, Choi and colleagues reported use of REGN-COV2 in a rituximab-treated patient who was critically ill with COVID-19 and aspergillus coinfection and died 11 days after administration [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On November 21, 2020, USFDA gave REGN-CoV-2 emergency approval for the treatment of mild or moderate COVID-19 symptoms in patients aged 12 and above (weighing at least 40 kg) and are at higher risk for developing severe COVID-19. This approval is based on the findings of a clinical trial that indicated a reduction in COVID-19-related hospitalization or emergency department visits in those at high risk of illness progression within 28 days of starting treatment [44] , [45] , [46] .…”
Section: Different Therapeutic Methods Towards Covid-19 Treatment And...mentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic continues to affect the global population. There have been several reports of immunocompromised patients developing persistent and prolonged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%